MIB1‐mediated degradation of WRN promotes cellular senescence in response to camptothecin treatment. Issue 9 (11th July 2020) - Li, Meiting; Liu, Boya; Yi, Jingjie; Yang, Yang; Wang, Jiadong; Zhu, Wei‐Guo; Luo, Jianyuan
Abstract: Werner syndrome protein (WRN) plays critical roles in DNA replication, recombination, and repair, as well as transcription and cellular senescence. Ubiquitination and degradation of WRN have been reported, however, the E3 ubiquitin ligase of WRN is little known. Here, we identify mindbomb E3 ubiquitin protein ligase 1 (MIB1) as a novel E3 ubiquitin ligase for WRN protein. MIB1 physically interacts with WRN in vitro and in vivo and induces ubiquitination and degradation of WRN in the ubiquitin‐proteasome pathway. Camptothecin (CPT) enhances the interaction between MIB1 and WRN, and promotes WRN degradation in a MIB1‐dependent manner. In addition, CPT‐induced cellular senescence is facilitated by the expression of MIB1 and attenuated by WRN expression. Our results show that MIB1‐mediated degradation of WRN promotes cellular senescence and reveal a novel model executed by MIB1 and WRN to regulate cellular senescence.